2018
DOI: 10.22616/erdev2018.17.n035
|View full text |Cite
|
Sign up to set email alerts
|

Diesel gas dual engine with liquid LPG injection into intake manifold

Abstract: Abstract. This paper presents an experimental research on the fuel control system which is installed on the diesel engine Cummins to assess the technical characteristics and emissions, when the engine is using dual fuel liquid LPG-Diesel with different ratios of LPG. The experimental results show that the engine running dual fuel LPG -Diesel reached 96 % maximum moment. Average torque and average power were reduced, but not significantly compared to the case of the engine using 100 % diesel. The percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…This means that these items may directly or indirectly collect, process and/or exchange data via a computer network and the Internet. Concurrently, other growing trends on a global scale are the advances in electromobility [2][3][4][5][6][7][8][9], obtaining energy from renewable sources and alternative fuels [10][11][12][13][14][15][16] and reducing exhaust emissions from means of transport [17][18][19][20][21][22][23][24]. The analysis of the literature and the state of knowledge confirmed that there are many technologies on the market for obtaining data from photovoltaic systems, electric car chargers and electricity meters taken from the power grid [2,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This means that these items may directly or indirectly collect, process and/or exchange data via a computer network and the Internet. Concurrently, other growing trends on a global scale are the advances in electromobility [2][3][4][5][6][7][8][9], obtaining energy from renewable sources and alternative fuels [10][11][12][13][14][15][16] and reducing exhaust emissions from means of transport [17][18][19][20][21][22][23][24]. The analysis of the literature and the state of knowledge confirmed that there are many technologies on the market for obtaining data from photovoltaic systems, electric car chargers and electricity meters taken from the power grid [2,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…We can say that biodiesel for use in diesel engines has become a substitute for diesel oil [39]. Furthermore, Dittrich et al [40] studied the fuel control system when an engine uses LPG-diesel dual fuel with different LPG proportions. They concluded that CO 2 and PM concentrations are reduced in dual-fuel vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing interest in electric vehicles, alternative fuels for piston combustion engines are constantly being developed. Gas fuels such as LPG for gasoline [15,16] and diesel engines [17,18], NG [19], CNG and LNG [20][21][22], various biofuels [23,24], and biodiesel from various raw materials [25][26][27][28][29][30] or hydrogenated vegetable oil (HVO) [31,32] are the examples of this progress. Another expanding field of research is related to fuel cells [33,34].…”
Section: Introductionmentioning
confidence: 99%